Capabilities of Native XML and Flat File Systems for Document Management - Mazlyda, Abdul Rahman (2004)
XML technology is becoming one of the rapidly growing technologies in this information technology era. The main advantage of XML is it could used for data transfer and data excange between different operating systens. It also enables creation of more meaningful tags, separates the content of a document from its presentation, which simplifies the development and maintenance, enable integration between data and documents, and the XML documents could be published in a variety of forms. Basically, to store and manage the XML and non-XML documents, not only native XML database could be used, but flat file database and the existing relational and object-oriented database could be used, but flat file database and the existing relational and object-oriented database could also be used as alternatives. However. besides those advantages, the problem on how to manage the documents and lack of guidelines on capabilities of those database in managing documents and lack of guidelines on capabilities of those databases in managing documents aroused. Therefore, this research is undertaken to study the capabilities of native XML and flat file database in managing documents, where each database has its own different methods. A prototype system had been developed and both XML document and non-XML document had been used as the testing data for the purpose of examining the capabilities of storing and retrieving techniques in both databases. Based on the result derived, a guideline on the capabilites of storing and retrieving those documents in native XML database and flat file database was proposed.